2017
DOI: 10.5489/cuaj.4340
|View full text |Cite
|
Sign up to set email alerts
|

Varicoceles in the pediatric population: Diagnosis, treatment, and outcomes

Abstract: Varicocele is commonly encountered in adolescents. There are still many controversies regarding pathophysiology, health effects, clinical significance, and optimum treatment of this condition. This article reviews the current evidence pertaining to children and adolescents with varicocele. This group present a unique and somehow challenging situation, since they are still going through pubertal changes that may confound the effects of the disease and its treatment on the developing testes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…The presence of varicocele has been postulated to affect testosterone production and, in turn, the hypothalamic-pituitary-gonadal axis. However, in terms of endocrine evaluation, the utility of obtaining a baseline hormonal evaluation for identifying adolescents at risk for infertility has not yet been demonstrated, and the significance of testosterone changes pre- and post-intervention remains unclear [ 27 ]. Multiple recent studies support a relationship between varicocele and the development of hypogonadism and androgen deficiency, potentially providing an impetus for early varicocele repair [ 28 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of varicocele has been postulated to affect testosterone production and, in turn, the hypothalamic-pituitary-gonadal axis. However, in terms of endocrine evaluation, the utility of obtaining a baseline hormonal evaluation for identifying adolescents at risk for infertility has not yet been demonstrated, and the significance of testosterone changes pre- and post-intervention remains unclear [ 27 ]. Multiple recent studies support a relationship between varicocele and the development of hypogonadism and androgen deficiency, potentially providing an impetus for early varicocele repair [ 28 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, endocrine evaluation in adolescents carries practical considerations. Immaturity of the hypothalamic-pituitary-gonadal axis in the different stages of development would demand different standards for evaluation 40 . Fideleff et al 41 performed a prospective study with 93 adolescents and found no difference in hormonal parameters of FSH, LH, Testosterone and GnRH from varicocele individuals and controls, even after correction of Tanner stage.…”
Section: Seminal Analysis and Hormonal Evaluationmentioning
confidence: 99%
“…This disease can cause an increase in reactive oxygen species and cause oxidative stress leading to sperm dysfunction (Heidari et al, 2016). Among men undergoing infertility investigation, approximately 30%-40% have varicocele (De Los Reyes, Locke, & Afshar, 2017;Punab et al, 2017;Sofimajidpour, Ghaderi, & Ganji, 2016). Among men undergoing infertility investigation, approximately 30%-40% have varicocele (De Los Reyes, Locke, & Afshar, 2017;Punab et al, 2017;Sofimajidpour, Ghaderi, & Ganji, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of varicocele is 4.4%-22.6% in the general population; however, it is present in 35%-44% of cases of primary infertility and in more than 45-81% of men with secondary infertility (Heidari et al, 2016;Jensen et al, 2017). Among men undergoing infertility investigation, approximately 30%-40% have varicocele (De Los Reyes, Locke, & Afshar, 2017;Punab et al, 2017;Sofimajidpour, Ghaderi, & Ganji, 2016).…”
Section: Introductionmentioning
confidence: 99%